2021
DOI: 10.5812/semj.115810
|View full text |Cite
|
Sign up to set email alerts
|

Brucellosis in Herat Province, Afghanistan: Epidemiological Status and Risk Factors

Abstract: Background: Human brucellosis, also known as Malta fever, is an acute systemic zoonotic disease in several parts of the world. The most pathogenic Brucella specie is Brucella melitensis that occurs in the human population of all age groups and of both sexes. Objectives: The present study aimed to investigate human Brucella infection in Afghanistan. Methods: The participants in this cross-sectional study were 44 patients diagnosed with Brucella infection during eight months and confirmed using Wright test by ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Brucellosis is known to be endemic in humans throughout Afghanistan, although a sharp decline was observed from 2007 (11.13/100,000) to 2019 (0.06/100,000). The latest survey revealed that the most affected patients were female housewives (40.9%) and students (18.18%) in Herat Province, Afghanistan, with the main route of transmission being the consumption of contaminated dairy products [ 22 ]. Brucellosis was introduced in Sri Lanka during the Second World War through the importation of cattle [ 23 ].…”
Section: Asiamentioning
confidence: 99%
“…Brucellosis is known to be endemic in humans throughout Afghanistan, although a sharp decline was observed from 2007 (11.13/100,000) to 2019 (0.06/100,000). The latest survey revealed that the most affected patients were female housewives (40.9%) and students (18.18%) in Herat Province, Afghanistan, with the main route of transmission being the consumption of contaminated dairy products [ 22 ]. Brucellosis was introduced in Sri Lanka during the Second World War through the importation of cattle [ 23 ].…”
Section: Asiamentioning
confidence: 99%